(2, 1)-total labelling of planar graphs with large maximum degree. (17th November 2017) - Yu, Yong; Zhang, Xin; Wang, Guanghui; Liu, Guizhen; Li, Jinbo
Abstract: In this paper, we prove for planar graph G with maximum degree Δ ≥ 12 that the (2, 1)-total labelling number λ 2 ( G ) is at most Δ + 2.